N-octanoyl dopamine inhibits the expression of a subset of κB regulated genes: potential role of p65 Ser276 phosphorylation. - Maximilia C Hottenrott; Johannes Wedel; Sophie Gaertner; Eleni Stamellou; Tineke Kraaij; Linda Mandel; Ralf Loesel; Carsten Sticht; Simone Hoeger; Lamia Ait-Hsiko; Angelika Schedel; Mathias Hafner; et al. (PLoS ONE, 2013)
Background and purpose Catechol containing compounds have anti-inflammatory properties, yet for catecholamines these properties are modest. Since we have previously demonstrated that the synthetic dopamine derivative N-octanoyl dopamine (NOD) has superior anti-inflammatory properties compared to dopamine, we tested NOD in more detail and sought to elucidate the molecular entities and underlying mechanism by which NOD down-regulates inflammation. Experimental approach Genome wide gene expression profiling of human umbilical vein endothelial cells (HUVECs) was performed after stimulation with TNF-α or in the combination with NOD. Confirmation of these differences, NFκB activation and the molecular entities that were required for the anti-inflammatory properties were assessed in subsequent experiments. Key results Down regulation of inflammatory genes by NOD occurred predominantly for κB regulated genes, however not all κB regulated genes were affected. These findings were explained by inhibition of RelA phosphorylation at Ser276. Leukocyte adherence to TNF-α stimulated HUVECs was inhibited by NOD and was reflected by a diminished expression of adhesion molecules on HUVECs. NOD induced HO-1 expression, but this was not required for inhibition of NFκB. The anti-inflammatory effect of NOD seems to involve the redox active catechol structure, although the redox active para-dihydroxy benzene containing compounds also displayed anti-inflammatory effects, provided that they were sufficiently hydrophobic. Conclusions and implications The present study highlighted important mechanisms and molecular entities by which dihydroxy benzene compounds exert their potential anti-inflammatory action. Since NOD does not have hemodynamic properties, NOD seems to be a promising candidate drug for the treatment of inflammatory diseases.